Assessment of the Impact of the Crisis on New PPI Projects - Update 4 : New Private Infrastructure Activity in Developing Countries Recovered in the First Half of 2009 Thanks to the Electricity Sector, But the Crisis Continues to Impact Projects - World Bank (World Bank, Washington, DC, 2012)
This review of new private participation in infrastructure (PPI) projects, covering the period up to June 2009, sheds some light on the recent activity and the short-term impact of the financial crisis, compared with the previous updates on the impact of the crisis, this note incorporates several improvements: a larger sample size (714 projects versus 522 in the previous update) over a longer period of time (from January 2008 to June 2009 compared to the previous update, which covered January 2008 to March 2009). The survey finds that the financial crisis significantly affected the rate of project closure rate of new PPI projects in the second half of 2008. The impact of the crisis varies across developing regions with Europe and Central Asia (ECA) being the most affected region so far. This analysis will be refined in the coming quarters to assess the extent to which these trends continue.